Agro-industrial waste management: a circular bioeconomy approach - Molina-Morejón, Víctor Manuel; Espinoza-Arellano, José de Jesús; Contreras-Martínez, Juan Gabriel; Díaz-Gurrola, Eyrán Roberto (Revista Mexicana de Ciencias Agrícolas, 2025)
This essay aimed to show how the management of agro-industrial waste can contribute not only to its valorization but also to the reduction of pollution, contributing to economic and environmental sustainability. The study was for the period from 2017 to 2024 in the region known as the Comarca Lagunera in north-central Mexico. At the beginning of this work, we present the results of a local process that, with its limitations, adds contextual value and regional applicability by treating waste, generating energy, and producing organic fertilizer and sustainably treated water. The improvement and updating of these local processes that started several years ago are compared to Ellen MacArthur’s butterfly diagram in a version adapted to the region’s dairy farms. The bibliographic review of experiences documented in scientific journals where the following is discussed: the extraction of valuable compounds before biodigestion, integrated anaerobic digestion and composting, the types of agro-industrial waste, the application for new generation biomass, and the analysis of the life cycle to evaluate the environmental impact. Finally, the valorization of waste for biorefinery and circular bioeconomy processes is highlighted. It was concluded that the bioeconomy offers benefits, although its adoption faces challenges, requiring complementation with economic studies, in particular, the design of efficient processes for the collection of valuable waste based on a supply chain that not only manages to make waste capture more agile but also efficient production and distribution processes.
Keywords: agro-industrial waste; biomass; composting